Upaya Pelestarian Natoni (Tuturanadat) dalam Budaya Timor Dawan (Atoni Meto) - Banamtuan, Maglon Ferdinand (Paradigma: Jurnal Kajian Budaya, 2022)
This research were aimed to describe natoni traditional speeches which were the reflection of Timor Dawan culture. This research used qualitative phenomenological approach. The research method used were antropological with survey means: observations and interviews. Results gained from this research were; natoni had been around since ancient time and still passed down to today’s generations; complete traditional costume were used when performing natoni. Regarding time and place to do natoni, data showed that natoni could be done at any time or place; natoni doers were traditional figures which understands natoni. Natoni is traditional speech in the form of poem which performed reciprocally; the aim of Natoni were as a homage and introduction to local culture; the values of natoni were universal. The structure of Natoni begins with initial phase which contained preparation and ended on closing phase with additional event of souvenir presentation. People were making efforts by continuosly presenting natoni performances in the communities so that natoni would become community custom.